Analisis Penerapan Digital Marketing UMKM Aneka Kue Basah Kaum Jaya - Septiana Wadiyastuti; Dedi Mulyadi (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
Digital marketing for a company is a very important part at this time. Culinary companies or MSME cakes are no exception, requiring good publications for their business's continuity and progress. In addition to having to compete with other MSMEs with tastes from delicious cakes to good service. In this digital era, many have used the marketplace, making reaching customers from various locations easier. Therefore, as umm kue kue Peru, it is necessary to organize or train to join the marketplace so that it can improve the business of these umm kue kue kuehs. While initially the target market was only targeted at students and the surrounding community, using digital marketing the target market has become wider.